The identification and economic content of ordered choice models with stochastic thresholds - Flavio Cunha; James Joseph Heckman; Salvador Navarro (Institute for the Study of Labor (IZA), 2007)
This paper extends the widely used ordered choice model by introducing stochastic thresholds and interval-specific outcomes. The model can be interpreted as a generalization of the GAFT (MPH) framework for discrete duration data that jointly models durations and outcomes associated with different stopping times. We establish conditions for nonparametric identification. We interpret the ordered choice model as a special case of a general discrete choice model and as a special case of a dynamic discrete choice model.
Keywords: 330; Diskrete Entscheidung; Stochastischer Prozess; Nichtparametrisches Verfahren; Theorie